“Las tic como herramienta pedagógica para la familiarización de las tecnologías digitales en niños de Educación Inicial” - Chusin Lema, Mónica Noemí (2023)
This research was approached the Technologies of Information and Communication as a pedagogical tool for the familiarization of digital technologies in children of initial education; it has as its objective to diagnose the frequency of the use of digital tools in the classroom; the investigation has a quantitative approach with a descriptive level, a deductive method allowing to know consequences and general conclusions, the used techniques were the survey and its instrument, the questionnaire, which focused on the opinion of parents and teachers, The observation with its checklist instrument was applied to the children in the class regarding emotions, sensory discrimination, corporal expression and motor skills; the main results were concentrated in the survey to teachers, so we have a considerable percentage of 80% that do not use digital resources to introduce children in the use of technology, since they do not have specialized tools or additional training to complement the learning of infants, to enhance the development of skills by promoting creativity and expression through videos, digital books, among other resources that awaken interest in learning creatively, Thus showing a change in the teaching-learning of both students and educators who seek to energize their classes with digital tools, generalizing the use and